Yerba Mate (Ilex paraguariensis A. St.‐Hil.) Reduces Oxidative Stress and Bone Resorption in Apical Periodontitis - Wajima, Carolina Sayuri [UNESP]; de Barros Morais Cardoso, Carolina [UNESP]; Anselmi, Caroline [UNESP]; Dal‐Fabbro, Renan; Ferraz, Murilo Catelani [UNESP]; da Silva, Cristiane Cantiga [UNESP]; Ciarlini, Paulo César [UNESP]; Ervolino, Edilson [UNESP]; Bottino, Marco Cícero; Cintra, Luciano Tavares Angelo [UNESP] (Wiley, 2025)
AIM: Apical periodontitis (AP) is a highly prevalent chronic inflammatory disease that can exert systemic effects by releasing biochemical mediators that initiate and regulate the immune response. Yerba Mate (Ilex paraguariensis, YM), a popular plant broadly consumed in South America, is rich in biologically active compounds known for their therapeutic potential. This study assessed Y's in vitro cytocompatibility, anti-osteoclastogenic and immunomodulatory effects on oral stem cells and macrophages, as well as its in vivo potential to reduce AP severity and systemic side effects. METHODOLOGY: In vitro, instant powdered YM was dissolved in distilled water, filtered and diluted in culture media to final concentrations ranging from 1 to 200 μg/mL. Cell viability and pro-inflammatory cytokine release (IL-1α, IL-6, TNF-α) were assessed in human exfoliated deciduous teeth stem cells. The NF-κB pathway and anti-osteoclastogenic activity were evaluated using a luciferase reporter assay and TRAP staining in RAW 264.7. Forty male Wistar rats were divided into control (C), YM-treated(YM), AP-induced (AP) and AP with YM treatment (AP + YM). YM treatment (20 Mg/Kg/Day) was administered via gavage for 58 days. AP was induced after 28 days of YM intake, and the animals were euthanised 30 days later. In serum, systemic redox state was assessed via total antioxidant capacity (TAC) and thiobarbituric acid reactive substances (TBARS). Histological and immunohistochemical analyses evaluated inflammation, cytokine expression (TNF-α, IL-6, IL-10 and IL-17) and bone resorption markers. Micro-CT quantified alveolar bone loss. Data were analysed at p < 0.05. RESULTS: YM treatment demonstrated significant anti-inflammatory, antioxidant and bone-protective effects. In vitro, YM-supported cell viability, reduced TNF-α and IL-1α, inhibited NF-κB activation and suppressed osteoclastogenesis. In vivo, YM treatment restored systemic antioxidant capacity and reduced lipid peroxidation, mitigating AP-induced oxidative stress. Furthermore, YM intake attenuated the local inflammatory response and reduced the bone resorptive activity associated with AP. CONCLUSION: In vitro, YM suppressed pro-inflammatory cytokines and NF-κB, inhibited osteoclastogenesis and was cytocompatible. In vivo, it reversed AP-induced redox state and reduced inflammation and bone resorption, suggesting therapeutic promise.